Long-term carbon emission reduction potential of building retrofits with dynamically changing electricity emission factors. (15th February 2022) - Lou, Yingli; Ye, Yunyang; Yang, Yizhi; Zuo, Wangda
Abstract: Buildings account for approximately 36% of the United States' total carbon emissions and building retrofits have great potential to reduce carbon emissions. Current research adopts a constant electricity emission factor although it changes over time due to the increase of renewable energy generation. To accurately predict emission reduction potential of building retrofits, this study develops a novel method by using dynamically changing electricity emission factors. Using medium office buildings as an example, we predicted emission reduction of eight building retrofit measures from 2020 to 2050 in five locations in the U.S. with distinct climates and renewable adoption rates. To evaluate emission reduction potential sensitivity to the compositions of electricity generation, five scenarios for renewable energy adoptions are investigated. The results reveal several new phenomena on emission reduction potential of building retrofits for medium offices in the U.S.: (1) it decreases from 2026 to 2050; (2) it has the same trend with coal usage; and (3) it reaches the maximum under the high renewable cost scenario. Based on the results, it is recommended that building retrofits should focus on 1) improving lighting and equipment efficiency; 2) locations with higher coal usage rate, and 3) buildings under the high renewable cost scenario. The new method can also be used for predicting emission reduction potential of the building sector in the U.S. by applying to other building types and regions. Highlights: Emission reduction potential (ERP) of building retrofit decreases from 2026 to 2050. Using constant emission factor will likely over-predict ERP in most locations. Renewable energy adoption scenarios and current adoption rate impact the ERP. Building retrofits have the highest impact on ERP under the HighReCost scenario.